2023
DOI: 10.1371/journal.pone.0284113
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a depression risk prediction nomogram for US Adults with hypertension, based on NHANES 2007–2018

Abstract: Depression is of increasing concern as its prevalence increases. Our study’s objective was to create and evaluate a nomogram to predict the likelihood that hypertension patients may experience depression. 13293 people with hypertension who were under 20 years old were chosen from the National Health and Nutrition Examination Survey (NHANES) database between 2007 and 2018 for this study. The training and validation sets were split up into the dataset at random in a 7:3 ratio. To find independent predictors, uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Studies have demonstrated that nomogram enable accurate compared to traditional scoring systems (Wang et al, 2021). It is now widely used for risk Frontiers in Pharmacology frontiersin.org prediction of many diseases (Li et al, 2021;Tan et al, 2022;Wang et al, 2023). Therefore, the creation of mortality risk nomogram based on the information about ATN patients can inform existing critical care assessment programs.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that nomogram enable accurate compared to traditional scoring systems (Wang et al, 2021). It is now widely used for risk Frontiers in Pharmacology frontiersin.org prediction of many diseases (Li et al, 2021;Tan et al, 2022;Wang et al, 2023). Therefore, the creation of mortality risk nomogram based on the information about ATN patients can inform existing critical care assessment programs.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has highlighted the modifiable association between the severity of depression and triglyceride levels, indicating a positive relationship with the high Framingham Risk Score. [ 26 , 27 ]…”
Section: Discussionmentioning
confidence: 99%
“…In our study, several potential factors that could influence the association between RDW and hypertension were carefully selected. These covariates include: Age (years), Gender (male/female),Race (Mexican American/ Other Race /Non-Hispanic White/Non-Hispanic Black),Body Mass Index (BMI, kg/m²),Waist circumference, Education level(≤11th Grade, High School, College, College above), Family poverty income ratio (PIR),Smoking status(Yes/No), Alcohol use; Presence of chronic conditions: Chronic congestive heart failure, Coronary heart disease(Angina pectoris, Heart attack), Stroke, Weak/failing kidneys, Diabetes, Chronic bronchitis, Emphysema, Thyroid disease; laboratory parameters: White blood cell count (1000 cells/uL), Lymphocyte number (1000 cells/uL), Red blood cell count (million cells/uL), Hemoglobin (g/dL), Hematocrit (%), Red cell distribution width (%), Platelet count (1000 cells/uL), Mean platelet volume (fL), Blood Urea Nitrogen (mmol/L), Total Calcium (mmol/L), Serum Cholesterol (mmol/L), Creatinine (umol/L), Glucose (mmol/L), Triglycerides (mmol/L), Uric acid (umol/L), Sodium (mmol/L), Potassium (mmol/L), LDL-cholesterol (mg/dL), HDL-cholesterol (mg/dL) [ 18 , 19 ]. These covariates were chosen to comprehensively account for potential confounding factors and ensure a robust analysis of the association between RDW and hypertension in our study.…”
Section: Methodsmentioning
confidence: 99%